1999
DOI: 10.1161/01.res.84.6.633
|View full text |Cite
|
Sign up to set email alerts
|

Signaling in Myocardial Hypertrophy

Abstract: C ardiac (ventricular) hypertrophy is an important adaptive response in vivo that (at least in the shorter term) allows the organism to maintain or increase its cardiac output. Global ventricular hypertrophy is a recognized response to increased pressure or volume work (reviewed in Reference 1), with increased myofibrillogenesis and sarcomere deposition being cardinal features. Although global hypertrophy is clinically important, probably the most significant form of cardiac hypertrophy in terms of patient num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
126
0
8

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(139 citation statements)
references
References 208 publications
(117 reference statements)
5
126
0
8
Order By: Relevance
“…32,33 RhoA is important for ERK1/2 activation in the mechanical stress-induced hypertrophy of cardiac myocytes. 17,34 Thus, the RhoA/Ras-ERK1/2 pathways are implicated in the signaling system that has a role in cardiac hypertrophy in response to hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32,33 RhoA is important for ERK1/2 activation in the mechanical stress-induced hypertrophy of cardiac myocytes. 17,34 Thus, the RhoA/Ras-ERK1/2 pathways are implicated in the signaling system that has a role in cardiac hypertrophy in response to hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…During direct activation by mechanical stress, G protein-coupled receptor agonists, such as angiotensin II, endothelin-1 and phenylepherine, activate the Ras-ERK cascade via protein kinase C activation and subsequently upregulate hypertrophic gene upregulation in cardiac myocytes. 32 In addition, angiotensin II and a-adrenergic agonists activate RhoA through Ga q /Ga 11 proteins in cardiac myocytes. 17,43 We have demonstrated that the cardiac angiotensin II system is activated in SAD-operated SHRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19]. Evidence is emerging that the p38 MAPK pathway is an important component of the cardiac cellular stress response.…”
mentioning
confidence: 99%
“…10 It is important to note that other signaling pathways such as the protein kinase C pathway or the mitogen-activated protein kinase (MAPK) cascade have also been shown to mediate the hypertrophic response in the heart. 11,12 Taken together, the majority of published evidence suggests that activation of the calcineurin signaling pathway, but not a reduction in I to density, is causally related to cardiac hypertrophy. Just when it seemed the matter was settled, Kassiri et al 13 report in this issue of Circulation Research that reduction of I tof in cultured neonatal rat ventricular myocytes causes hypertrophy via a calcineurin-dependent pathway.…”
mentioning
confidence: 99%